Analisis Perubahan Dampak Pandemi Covid-19 dalam Proses Mewujudkan Karakter pada Pelajar Pancasila - Rahman Sunanda; Dessy Wardiah; Aldora Pratama (Departement of Mathematics Education, 2023)
This study aims to describe the changes in learning experienced by teachers and students. In this study focused on qualitative research. The method used here is descriptive method in conducting the analysis. The data collection techniques here are through interviews, observations, questionnaires and documentation. The data analysis technique here uses a qualitative descriptive analysis technique which is presented in the form of splitting or parsing data that will produce appropriate data. From the results of the study, it was shown that learning changes were caused by the Covid-19 pandemic, precisely in Grade 6 students at SD Negeri 04 Palembang, which still had many shortcomings caused by the pandemic, which made students difficult to accept learning, lack of focus or feel confused and difficult to understand. material and do not pay attention to the teacher when learning takes place. There is a sensitive attitude shown by these students during learning. The changes faced due to the Covid-19 Virus certainly have a lot of negative impacts on the learning process this year, especially students. From the overall results obtained in this study it can be seen that the impact of this pandemic also occurred due to internal factors and external factors, which internal factors themselves occurred in the children themselves who might lack interest in learning, as well as for external factors such as the environment. Families who do not provide enough support for their children. From the above results the learning process experienced after this pandemic has greatly decreased, based on what is produced from research here teachers and students must be good at communicating so that learning can run smoothly, and teachers must be able to provide material well.